The Effect of Functional Nasal Surgery on Olfactory Function. Issue 3 (23rd February 2021) - Pfaff, Miles J.; Bertrand, Anthony A.; Lipman, Kelsey J.; Shah, Aloukika; Nolan, Ian; Krishna, Vikram; Patel, Harsh; Roostaeian, Jason; Lee, Justine C.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Functional and aesthetic nasal operations are some of the most common plastic surgery procedures performed in the United States. The purpose of the study was to evaluate the effects of septoplasty, septorhinoplasty, and rhinoplasty procedures on postoperative olfactory function and their relationship to nasal airflow and quality of life. Methods: A systematic review and meta-analysis was performed evaluating olfactory function following nasal surgery. Preoperative and postoperative values for olfaction, nasal airflow, and quality of life/nasal symptoms were analyzed. The effect size was calculated from each study and used for meta-analysis. As studies evaluated patients at different points in the postoperative period, the latest time point reported by each study was used in the meta-analysis. The 95 percent confidence interval of the effect size was calculated for each study. Study quality was assessed using the Jadad and Methodological Index for Nonrandomized Studies instruments. All included studies were Level of Evidence II. Results: There were 25 included studies. Following nasal surgery, patients experienced significant improvements in olfaction ( p < 0.001), nasal airflow ( p < 0.001), and quality of life/nasal symptoms ( p < 0.001). Patients often experienced a transient decrease in olfaction immediately after surgery, followed by improvement postoperatively. Preoperative olfactory dysfunction rates were low and postoperative dysfunction was equally low. Olfaction improvement was directly correlated with improvement in nasal airflow and quality of life. Conclusions: Functional and aesthetic nasal operations appear to significantly improve olfaction, which is directly correlated with nasal airflow. Some studies report a transient worsening of these measures in the immediate postoperative period, which subsequently improved at later time points.